SYSTEMIC ANALYSIS OF microRNAs ACTIVITY IN TUMOR GROWTH - Mintser, O.P.; Zaliskyi, V. M.; Malyarchuk, Ye. A. (Medical Informatics and Engineering, 2020)
Background. Some data on the role of miRNAs are conceptualized. When analyzing possible strategies for restoring the normal level of p53 and p53-dependent microRNAs in order to prevent malignant neoplasms, it was suggested that the detected veils changed the understanding of gene expression and set a precedent for the development of new methods for the diagnosis and treatment of cancer. It is important to identify additional potential microRNAs targets and develop safe microRNA-based treatment methods so that microRNAs modulation becomes a critical method for the treatment and treatment of cancer. In this regard, the studied variants of anticancer therapy associated with the simultaneous hyperactivation of two apoptosis regulators, p53 and microRNAs, are of interest. Materials and methods. Results. Within the framework of the accepted mathematical modeling, a potentially high anti-blastoma therapy is shown, the target of which is the p53 inhibitor protein as the main link of the p53 positive feedback loop-miRNA, as well as the initiation of tumor metastasis. Conclusions are drawn: 1. MicroRNAs are the most important regulators of cell differentiation, proliferation, and survival. Changes in miRNA expression are clearly associated with the progression of numerous human diseases, in particular cancer. 2. MicroRNAs play a key role in the genesis of tumors as important modulators/demodulators in cell pathways, regulating target gene expression through repression or mRNA degradation. Conclusions. MicroRNAs are attractive candidates for the role of prognostic biomarkers and therapeutic targets in cancer.